A study on the element of sentiment toward knowledge sharing among knowledge workers in a virtual CoP - Ng, Chuee Leng; Lee, Angela Siew Hoong *; Lim, Tong Ming * (International Foundation for Research & Development, 2013)
Ever since the usage of alternative media has grown tremendously, it was seen that the increasing amount of interactive online sites that are categorized as Web 2.0 systems has changed the communication and collaboration among knowledge workers. These systems provide greater interactivity and higher user-generated content. Social networking site is one type of online platforms that allow people to collaborate and communicate through a variety of services for social purposes (Broughton, Higgins, Hicks, & Cox, 2009). These high-flying social networking sites are driving new forms of social interaction, allowing users to intermingle and cooperate with each other in a social media dialogue nowadays by swapping ideas or posting updates and comments. It is crucial to comprehend how social relationships affect the content share between each knowledge worker in a virtual world. This project investigates how work and friend relationships can influence the utilization of social media systems for knowledge sharing. The effect of the element of sentiment among knowledge workers in a virtual Community of Practice (CoP) as they send and receive messages with their peers will be studied in this research. Different forms of emotion from knowledge workers will be investigated in this study in the workplace. A proposed research model will be proposed. A research framework will be outlined and qualitative and quantitative analysis will be used to analyze the research results.